Agrární politik František Udržal v roce ustavení Československa - Charbuský, Miloš (Univerzita Pardubice, 2002)
Prominent Czech agrarian politician František Udržal identified himself with the idea of announcement of independent Czechoslovak state. He contributed to its realisation both by his acting in the Vienna parlament, and by his acting in Prague. He was involved directly in formation of Czechoslovak republic 29. october. Taking into consideration his original antiaustrian orientation he gradually started to live in seclusion.
Keywords: agrární politika; Udržal, František; 1918; nezávislost